Shape-memory polymers and multifunctional composites - Leng, Jinsong; Du, Shanyi (Taylor & Francis, 2010)
Admired for their extraordinary stimuli-sensitive behavior and shape-changing capabilities, shape-memory polymers (SMPs) and multifunctional composites are among the most important smart materials. They continue to be widely applied in many diverse fields to create things such as self-deployable spacecraft structures, morphing structures, SMP foams, smart textiles, and intelligent medical devices. Written by renowned authors, Shape-Memory Polymers and Multifunctional Composites is a broad overview of the systematic progress associated with this emerging class of mate.